2009
DOI: 10.1086/605320
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Hub Systems with Protected Connections and the Reduction of Risk of Catheter-Related Bloodstream Infection in Pediatric Patients Receiving Intravenous Prostanoid Therapy for Pulmonary Hypertension

Abstract: BACKGROUND Intravenous prostanoids (epoprostenol and treprostinil) are effective therapies for pulmonary arterial hypertension but carry a risk of catheter-related bloodstream infection (CR-BSI). Prevention of CR-BSI during long-term use of indwelling central venous catheters is important. OBJECTIVE To evaluate whether using a closed-hub system and waterproofing catheter hub connections reduces the rate of CR-BSI per 1,000 catheter-days. DESIGN Single-center open observational study (January 2003–December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 18 publications
3
51
0
3
Order By: Relevance
“…We aimed to better understand these CVL complications by reviewing our experience with this therapy. Our overall rate of CVL-BSI (0.25 cases per 1,000 catheter-days) is remarkably similar to that reported by Ivy et al 6 among pediatric patients after instituting enhanced preventative measures (0.24 cases per 1,000 catheter-days), although we report a greater number of CVL-days (43,855 vs. 8,308). The REVEAL registry reported that the rate of CVL-BSI for patients ≤18 years old (n ¼ 83 patients; the number of patient-days was not given) was no different than the rate for adults (0.20 cases per 1,000 CVL-days), but the exact number was not given.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We aimed to better understand these CVL complications by reviewing our experience with this therapy. Our overall rate of CVL-BSI (0.25 cases per 1,000 catheter-days) is remarkably similar to that reported by Ivy et al 6 among pediatric patients after instituting enhanced preventative measures (0.24 cases per 1,000 catheter-days), although we report a greater number of CVL-days (43,855 vs. 8,308). The REVEAL registry reported that the rate of CVL-BSI for patients ≤18 years old (n ¼ 83 patients; the number of patient-days was not given) was no different than the rate for adults (0.20 cases per 1,000 CVL-days), but the exact number was not given.…”
Section: Discussionsupporting
confidence: 90%
“…There are multiple reports focused on CVL-related bloodstream infections (BSIs) in adults [2][3][4][5] but only a single report regarding CVL-BSI with PGI 2 infusion in mostly pediatric patients (although the age of the patients is not given), 6 and we know of no information regarding the incidence of other complications (e.g., CVL superficial infection, fracture, displacement, and occlusion) in this setting. Children may be at different risk than adults for CVL complications owing to high activity levels, being less mindful of the need for CVL protection, and possibly other factors.…”
mentioning
confidence: 99%
“…312,313 Recently, the use of specific closed-hub systems has been described in children to decrease the risk of catheter-related infection. 314 Some children have an exceptional clinical response to intravenous epoprostenol, which includes near normalization of PAP. This subset of children may eventually be transitioned from intravenous to oral therapy with close monitoring.…”
Section: Pgi 2 Analogsmentioning
confidence: 99%
“…An increase in catheter-related and Gram-negative bloodstream infections among patients with PAH treated with intravenous treprostinil has been noted, but this risk may be mitigated by using watertight seals throughout the delivery system, using closed-hub systems, and changing the diluent of treprostinil to epoprostenol diluent. 313,314,321,322 Intravenous treprostinil may have fewer side effects than intravenous epoprostenol, but no studies have directly compared both agents. 323 Treprostinil has also been given in an inhaled form, 324 and studies have recently been published in children.…”
Section: Pgi 2 Analogsmentioning
confidence: 99%
“…However, similarities between adult and pediatric PAH and compelling observational data (Yung et al, 2004;Lammers et al, 2007) have led to a consensus that epoprostenol provides significant benefit in children with idiopathic PAH, heritable PAH, and PAH associated with congenital heart disease (Barst et al, 2011a). As with adults, line dislodgement, local infection, and sepsis remain significant concerns (Doran et al, 2008;Ivy et al, 2009).…”
Section: Approved Drugsmentioning
confidence: 99%